Species diversity and conservation significance of mammal fauna in Du Gia - Khau Ca area, Ha Giang province - Dang, Nguyen Xuan; Nghia, Nguyen Xuan; Duy, Nguyen Dinh (Academia Journal of Biology, 2014)
Study area consists of 2 protected areas in Ha Giang Province with poor surveys on biodiversity values: Du Gia Nature Reserve (11,795 ha) with domination of lowland, montane tropical evergreen forest and small area of limestone evergreen forest. Khau Ca species habitat Tonkin snub-nosed monkey conservation area (2,024 ha) is predominated by limestone evergreen forest. This study has recorded 59 mammal species belonging to 22 families and 9 orders. Additionally, eight (8) species of bats has been recorded by other authors that increases the list to 67 species of 22 families and 9 orders. Study area has high conservation significance, there are 16 species enlisted in Vietnam Red Data Book and 8 species enlisted in 2013 IUCN Red List at CR, EN and Vu categories. Especially, the study area harbors the world largest population of Tonkin Snub-nosed Monkey Rhinopithecus avunculus (in Khau Ca Species Habitat Tonkin Snub-nosed Monkey Conservation Area) and possibly also nationally largest population of Francois langur Trachypithecus francoisi (in Du Gia Nature Reserve). These species are highly threatened both in Vietnam and globally. Pressure of adverse impacts on biodiversity in study area remains at high level including wildlife hunting and trade, forest destruction for agricultivation, illegally harvesting timber and non-timber forest products, free ranging cattle raising inside protected areas and especially intensive commercial mining throughout the area.